Different Role Perceptions and Practices Among Israeli High School Homeroom Educators and Subject Teachers - Bar Gosen, Noah (My University, 2018)
W izraelskim systemie edukacyjnym istnieją dwie zdefiniowane zawodowe role nauczycieli: wychowawcy, którzy koncentrują się na aspektach wychowawczych i nauczycielach przedmiotowych, którzy koncentrują się na kwestach dydaktycznych (Ministerstwo Edukacji, rozporządzenie w sprawie służby personelu, 2018). Badania miały na celu eksplorację postrzegania swojej roli przez te dwie grupy nauczycieli. W badaniach przyjęto podejście triangulacyjne. Najpierw odbyły się półstrukturalne wywiady z 12 wychowawcami. Jakościowa analiza danych stanowiła podstawę kwestionariusza do badań kwestionariuszowych nauczycieli (N = 130). Wyniki pokazały różnice między tymi dwoma grupami nauczycieli, w obszarze celów i zadań zawodowych, holistycznego spojrzenia na swoich uczniów; roli nauczania, oraz relacji z rodzicami uczniów. Wyniki nie wykazały istotnych różnic w statusie szkolnym, częstotliwościach zachowań zakłócających, wdrażaniu praktyk instruktażowych i określaniu wyzwań zawodowych. Zaleca się adaptacje procesów przygotowawczych nauczycieli do obydwu ról, a także sposoby współpracy między tymi grupami. Warto prowadzić dalsze badania ze szczególnym uwzględnieniem percepcji własnej roli przez nauczycieli.

There are two defined teachers' professional roles in the Israeli educational system: homeroom educators who focused on educational aspects and subject teachers who focused on instructional aspects (Ministry of Education, Instruction Personnel Service Regulation, 2018). Current research aims to investigate different role perceptions and practices among Israeli high school homeroom educators and subject teachers. Chosen research approach was triangulation. First, semi-structured interviews were held with 12 high school instructional personnel, regarding their role perceptions and practices. Qualitative data analysis set the basis for a quantitative questionnaire, which questioned teachers' perception and practices in various domains (N=130). Results showed differences between teachers from both roles, regarding their emphasis on educational and instructional goals, holistic view of their students; their main teaching roles; the usage of educational practices; and the sustainment of ongoing relationships with students' parents. Results did not show significant differences in school status, frequencies of disruptive behavior, the implementation of instructional practices and idnetifying challanging characters of students and students ' parents. Adaptations of teachers' preparatory processes for role differentiation, is advised, as well as cooperation modes between these professional roles. Further research held in a more concised and controlled manner is recomannded, including special emphasis on subject teachers' role characteristics and perceptions.
Wydział Studiów Edukacyjnych
Keywords: pedeutologia; pedeutology; role nauczycieli; teacher roles; wychowawcy; homeroom educators; nauczyciele przedmiotowi; subject teachers